Perception of local community on the indicators of governance in Tanjung Piai National Park - Rozak, Nurul Izatul Natasya (2016)
Concerned with the rapid depletion of the mangrove and wetland ecosystems in Tanjung Piai National Park, a RAMSAR site, Johore, relevant government agencies are normally created and given the responsibilities to ensure that the establishment of the protected areas will achieve the objectives of protecting the ecosystem which are of national and perhaps of international interests. This research discusses the perception of local community of Tanjung Piai on role of good governance and community participation as tools to make environmental enforcement happen in Tanjung Piai National Park (TPNP). The findings of this research were based on structured questionnaire which by Likert Scale. They are categorised into 28 factors of 7 dimensions: Indicators of Governance, Management and Administration, Information and Knowledge, Policy and Plan, Environmental and Natural Resources, Facility and Infrastructure and Finance and Budget. Factor Analysis is used in this study to regrouping the question that significant with this research while Multiple Linear Regression Analysis is used to determine the factor affecting perception on governance roles in local community perception. By using Descriptive Analysis, a percentage and frequency for socio-demographic and mean for dependent and independent variable showed the overall image of the distribution data. With regard to a valid analysis reference, the study outcome can be applied to be the deciding factor in choosing the good governance guidelines for wetlands conservation that involving the participation of local community. Therefore, to achieve a conservation of wetlands, proper governance is recommended and better enforcement of the law is needed.